Disentangling formation of multiple-core holes in aminophenol molecules exposed to bright X-FEL radiation. (28th October 2015) - Zhaunerchyk, V; Kamińska, M; Mucke, M; Squibb, R J; Eland, J H D; Piancastelli, M N; Frasinski, L J; Grilj, J; Koch, M; McFarland, B K; Sistrunk, E; Gühr, M; et al.
Abstract: Competing multi-photon ionization processes, some leading to the formation of double core hole states, have been examined in 4-aminophenol. The experiments used the linac coherent light source (LCLS) x-ray free electron laser, in combination with a time-of-flight magnetic bottle electron spectrometer and the correlation analysis method of covariance mapping. The results imply that 4-aminophenol molecules exposed to the focused x-ray pulses of the LCLS sequentially absorb more than two x-ray photons, resulting in the formation of multiple core holes as well as in the sequential removal of photoelectrons and Auger electrons (so-called PAPA sequences).